2008
DOI: 10.1002/dvdy.21616
|View full text |Cite
|
Sign up to set email alerts
|

Btg1 and Btg2 gene expression during early chick development

Abstract: Btg/Tob genes encode for a new family of proteins with antiproliferative functions, which are also able to stimulate cell differentiation. Btg1 and Btg2 are the most closely related members in terms of gene sequence. We analyzed their expression patterns in avian embryos by in situ hybridization, from embryonic day 1 to 3. Btg1 was distinctively expressed in the Hensen's node, the notochord, the cardiogenic mesoderm, the lens vesicle, and in the apical ectodermal ridge and mesenchyme of the limb buds. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…BTG2 belongs to the anti-proliferative gene family and has been shown to be involved in cell growth, differentiation and survival (Mo et al 2011), muscle fibre size, intramuscular fat deposition and weight loss (Kamaid and Giráldez 2008;Sasaki et al 2006). FA analyses demonstrated that x-3 and x-6 FAs increased in the liver of lambs supplemented at 10 and 20 % Spirulina levels.…”
Section: Discussionmentioning
confidence: 97%
“…BTG2 belongs to the anti-proliferative gene family and has been shown to be involved in cell growth, differentiation and survival (Mo et al 2011), muscle fibre size, intramuscular fat deposition and weight loss (Kamaid and Giráldez 2008;Sasaki et al 2006). FA analyses demonstrated that x-3 and x-6 FAs increased in the liver of lambs supplemented at 10 and 20 % Spirulina levels.…”
Section: Discussionmentioning
confidence: 97%
“…SIRT1, which was shown to be upregulated after irradiation, promotes transient and constituent Wnt signaling through regulation of Dishevelled proteins [ 66 ]. KRAS, HDAC1 and BTG2 (upregulated in the gene expression analysis) and p21 (upregulated using immunoblotting) are known to stimulate Wnt signaling [ 67 69 ]. SIAH-1 (upregulated in the gene expression analysis) is also activating Wnt signaling through activation of ß-catenin by ubiquitination [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Btg1 induces avian myoblast differentiation (Marchal et al, 1995; Rodier et al, 1999) and the development of endothelial cells (Iwai et al, 2004) and is also likely involved in the differentiation of sperm cells (Raburn et al, 1995). Btg1 is expressed in the developing and adult brain (Su et al, 2004; Kamaid and Giráldez, 2008), but no information on its function in neural tissues is available. Thus, we generated Btg1 knock out mice and analyzed the functional contribution by Btg1 to the adult neurogenic niches of the hippocampus and SVZ (Zhao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%